Illocutionary Acts Of The Antagonist In The Menu (2022) - Annisa Camilla Rahmayani (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
This study aims to analyze the illocutionary acts found in the utterances of the antagonist character in The Menu (2022) to find out the reason why the acts are used and to find out which five functions of illocutionary acts are frequently used in the movie. This study used qualitative research. Through an analysis of speech acts, conversational implicatures, and contextual cues, this study investigates the nuances of language usage by antagonistic figures. By deciphering their illocutionary acts, this research seeks to illuminate the intricate interplay between linguistic maneuvers, character motives, and their impact on the narrative structure. The result of this study; there are 49 statements with illocutionary acts in them. Based on Searle's classification of illocutionary acts, these statements are split into five groups. Six expressive utterances, three declarative utterances, one commissive statement, 16 representational utterances, and 23 directive utterances are all present. The dominant illocutionary acts that occurred in the movie is directive utterances 26 data.